Impact of COVID-19 pandemic on major depressive disorder in acute psychiatric inpatients - Brasso, Claudio; Cisotto, Marta; Del Favero, Elisa; Giordano, Benedetta; Villari, Vincenzo; Rocca, Paola (Frontiers in Psychology, 2023)
The spread of the coronavirus disease 2019 (COVID-19) pandemic and the subsequent restrictions significantly affected mental health, especially major depressive disorder (MDD) whose incidence increased by 27.6% in 2020, after the COVID-19 outbreak. Few studies focused on the impact of the pandemic on the clinical characteristics of outpatients with MDD and even fewer on inpatients admitted for a major depressive episode (MDE). We aimed to compare the characteristics of MDD of two groups of patients admitted for a MDE before and after the pandemic outbreak and to investigate which variables are significantly related to post-lockdown hospitalizations. This retrospective study included 314 patients with MDD hospitalized from January 2018 to December 2021 for a MDE (DSM-5) before (n = 154) and after (n = 160) the Italian lockdown (9th of March 2020). We compared patients’ sociodemographic and clinical characteristics. The characteristics significantly different between the two groups were included in a logistic regression to identify the factors more strictly associated with post-lockdown hospitalizations. During post-lockdown hospitalizations, we found a higher rate of severe MDE, MDE with psychotic features , and suicidal ideation , a lower proportion of patients followed by psychiatric services before admission, a higher percentage of them in treatment with psychotherapy and more frequent increase of the antidepressant dosage and adoption of augmentation strategies to treat the MDE. In the regression model, post-lockdown hospitalizations were significantly associated with suicidal ideation (OR = 1.86; p = .016) and psychotic features (OR = 4.41; p = .029) at admission, the increase in the antidepressant daily dose (OR = 2.45; p = .009), and the employment of an augmentation therapy (OR = 2.25; p = .029). These results showed an association between the COVID-19 pandemic and the occurrence of MDE with more severe clinical features. This might be true also for future calamities, suggesting that in these emergency contexts patients with MDD would require more attention, resources, and intense treatments with a specific focus on suicide prevention.